Pengaruh Ukuran Perusahaan, Risiko Perusahaan, dan Profitabilitas Klien Terhadap Audit Fee - Fisabilillah, Pra Dhita; Fahria, Rahmasari; Praptiningsih, Praptiningsih (Institut Bisnis dan Informatika Kesatuan, 2020)
This research is a quantitative study that aims to determine the effect of company size, company risk, and client profitability on audit fees. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period of 2016-2018 which were selected using purposive samples. The number of observations is 99 samples. The analysis technique used in this study is multiple linear regression analysis using SPSS 25 software with a significance level of 5%. The results of the test show that (1) company size has a positive effect on audit fees (2) company risk has no effect on audit fees, and (3) client profitability has a positive effect on audit fees. Keywords: Company Size, Company Risk, Client Profitability, Audit Fee